Aberrant Right Posterior Sectoral Duct Draining in Cystic Duct - An Interesting Intraoperative Challenge - Aniruddha Bhosale; Akhileshwar Singh (International Journal of Anatomy Radiology and Surgery, 2018)
Misinterpretation of intraoperative biliary anatomy is the most common cause of biliary injuries during laparoscopic cholecystectomy. These potentially avoidable injuries may lead to considerable morbidities in the form of biliary leaks, sepsis, jaundice or cirrhosis. Clear knowledge of biliary anatomy and strict adherence to the principles of surgery can avoid most of these injuries. Many variations in bile duct anatomy are seen but the most important from an operative view point are those pertaining to the cystic duct and right sectoral ducts. Right posterior sectoral ducts draining into cystic duct are potentially dangerous and very rare. The reported incidence of this anomaly is less than 2.9%. We report a similar case from our department, where during laparoscopic cholecystectomy an aberrant right posterior sectoral duct was encountered draining into cystic duct just distal to the neck of gallbladder. Cholecystectomy was completed laparoscopically with no post-operative complications.